Enhanced immunogenicity of an HIV-1 DNA vaccine delivered with electroporation via combined intramuscular and intradermal routes - Mann,JFS; Mckay,PF; Fiserova,A; Klein,K; Cope,A; Rogers,P; Swales,J; Seaman,MS; Combadiere,B; Shattock,RJ (Journal of Virology, 2014)
It is accepted that an effective prophylactic HIV-1 vaccine is likely to have the greatest impact on viral transmission rates. As previous reports have implicated DNA-priming, protein boost regimens to be efficient activators of humoral responses, we sought to optimize this regimen to further augment vaccine immunogenicity. Here we evaluated single versus concurrent intradermal (i.d.) and intramuscular (i.m.) vaccinations as a DNA-priming strategy for their abilities to elicit humoral and cellular responses against a model HIV-1 vaccine antigen, CN54-gp140. To further augment vaccine-elicited T and B cell responses, we enhanced cellular transfection with electroporation and then boosted the DNA-primed responses with homologous protein delivered subcutaneously (s.c.), intranasally (i.n.), i.m., or transcutaneously (t.c.). In mice, the concurrent priming regimen resulted in significantly elevated gamma interferon T cell responses and high-avidity antigen-specific IgG B cell responses, a hallmark of B cell maturation. Protein boosting of the concurrent DNA strategy further enhanced IgG concentrations but had little impact on T cell reactivity. Interestingly protein boosting by the subcutaneous route increased antibody avidity to a greater extent than protein boosting by either the i.m., i.n., or t.c. route, suggesting that this route may be preferential for driving B cell maturation. Using an alternative and larger animal model, the rabbit, we found the concurrent DNA-priming strategy followed by s.c. protein boosting to again be capable of eliciting high-avidity humoral responses and to also be able to neutralize HIV-1 pseudoviruses from diverse clades (clades A, B, and C). Taken together, we show that concurrent multiple-route DNA vaccinations induce strong cellular immunity, in addition to potent and high-avidity humoral immune responses.